Intraluminal irradiation for the palliation of lung cancer with the high dose rate micro-Selectron. Issue 10 (October 1990) - Burt, P A; O'Driscoll, B R; Notley, H M; Barber, P V; Stout, R
Abstract : Fifty patients with inoperable, symptomatic endobronchial carcinoma were treated by a single exposure of intraluminal radiotherapy. A high dose rate afterloading system (the micro-Selectron-HDR) was used to minimise radiation exposure for staff. Haemoptysis was relieved in 24 of 28 patients, breathlessness in 21 of 33 patients, and cough in nine of 18 patients. Radiological collapse resolved in 11 of 24 patients. Treatment was given on an outpatient basis and was well tolerated. Intraluminal radiotherapy appears to offer an effective alternative to conventional fractionated external beam radiotherapy.